Improved DTC strategy of an electric vehicle with four in-wheels induction motor drive 4WDEV using fuzzy logic control - Nair Nouria; Gasbaoui Brahim Ghazouni Abdelkader; Benoudjafer Cherif (Institute of Advanced Engineering and Science, 2021)
In this paper, we will study a four-wheel drive electric vehicle (4WDEV)with two control strategies: conventional direct torque control CDTC and DTC based on fuzzy logic (DTFC). Our overall idea in this work is to show that the 4WDEV equipped with four induction motors providing the drive of the driving wheels controlled by the direct fuzzy torque control ensures good stability of the 4WDEV in the different topologies of the road, bends and slopes. and increases the range of the electric vehicle. Numerical simulations were performed on an electric vehicle powered by four 15 kW induction motors integrated into the wheels using the MATLAB / Simulink environment, where the reference speeds of each wheel (front and rear) are obtained using an electronic speed differential (ESD). This can eventually cause it to synchronize the wheel speeds in any curve. The speed of each wheel is controlled by two types of PI and FLC controllers to improve stability and speed response (in terms of setpoint tracking, disturbance rejection and climb time). Simulation results show that the proposed FLC control strategy reduces torque, flux and stator current ripple. While the4WDEV range was improved throughout the driving cycle and battery power consumption was reduced.